Insight into plant cell wall chemistry and structure by combination of multiphoton microscopy with Raman imaging. Issue 4 (1st December 2017) - Heiner, Zsuzsanna; Zeise, Ingrid; Elbaum, Rivka; Kneipp, Janina
Abstract : Spontaneous Raman scattering microspectroscopy, second harmonic generation (SHG) and 2‐photon excited fluorescence (2PF) were used in combination to characterize the morphology together with the chemical composition of the cell wall in native plant tissues. As the data obtained with unstained sections of Sorghum bicolor root and leaf tissues illustrate, nonresonant as well as pre‐resonant Raman microscopy in combination with hyperspectral analysis reveals details about the distribution and composition of the major cell wall constituents. Multivariate analysis of the Raman data allows separation of different tissue regions, specifically the endodermis, xylem and lumen. The orientation of cellulose microfibrils is obtained from polarization‐resolved SHG signals. Furthermore, 2‐photon autofluorescence images can be used to image lignification. The combined compositional, morphological and orientational information in the proposed coupling of SHG, Raman imaging and 2PF presents an extension of existing vibrational microspectroscopic imaging and multiphoton microscopic approaches not only for plant tissues. Abstract : Spontaneous Raman, polarization‐resolved second harmonic generation (SHG) and 2‐photon excited fluorescence were used simultaneously for multimodal mapping to obtain chemical, structural and orientational information of cell walls in sorghum leaf and root cross‐sections, extending current vibrational imaging and multiphoton microscopies. The distribution of chemical components and the structure of the cell walls were investigated with the help of multivariate methods, and the use of polarization‐resolved SHG signals revealed the supramolecular structure of the cell walls.